How the forcing dynamics of the western boundary currents in the Pacific respond to the North Equatorial Current. (January 2023) - Li, Junlu; Gan, Jianping
Highlights: The intensity and variability of the KC and MC are associated with the circulation in the northern and southern NKM sub-domains, respectively. Planetary vorticity fluxes within the currents dominate the circulation in the two sub-domains, and nonlinearity due to relative vorticity convergence/divergence mainly consumes the circulation. The bottom pressure torque caused by isopycnal tilting in the western boundary region and local wind stress curl jointly modulate the circulation. Abstract: Applying a layer-integrated vorticity balance to the North Equatorial Current (NEC) -Kuroshio Current (KC)-Mindanao Current (MC) system, we found that the intensities of the circulations composed by NEC-KC and NEC-MC in the corresponding northern and southern NEC-KC-MC (NKM) sub-domains control the KC and MC, respectively. The planetary vorticity fluxes associated with the NEC, KC, and MC volume transports externally dominates the inter-linked NKM circulations, and the prominent nonlinearities with the western boundary currents internally determine the dynamic response. The net planetary vorticity loss in the northward KC and vorticity gain in the westward NEC dominate the vorticity budget in their respective sub-domains and subsequently lead to a corresponding relative vorticity convergence and divergence in the downstream-accelerating KC and MC. Imparts of the negative/positive vorticity from wind stress curl (WSC) accelerate/decelerate the KC, while the positive vorticity impart from the WSC accelerates the MC throughout the year. Bottom pressure torque produced by tilting isopycnals contributes an amount comparable to what the WSC contributes to the circulation in the western boundary region. This study reveals the connection between the KC/MC and the corresponding regional circulations and advances our understanding of the underlying mechanisms in the NKM system and quantifies the interacting external/intrinsic physical inter-connection. This dynamic study is a companion to Li and Gan's (2022) kinematic study where they investigated what the NKM modes of three physical features: intensity, migration, and bifurcation location contribute to the transports of the KC and the MC.